Medical-Device Related Pressure Injuries to Children in the Intensive Care Unit. (30th November 2017) - Widiati, Eka; Nurhaeni, Nani; Gayatri, Dewi
ABSTRACT: Medical devices that are attached to children put pressure on their skin or mucous membranes, and the devices can lead to injuries. The objective of this study was to determine the effectiveness of injury-prevention guidance about children who need to have medical devices attached to their bodies as part of their treatment. The research used a randomized controlled trial method, along with a cross-over design in 50 respondents with age ranges from 1 day to 18 years. The control group was treated in accordance to hospital routine, while the intervention group was given medical treatment based on Kiss and Heiler's guidelines. Skin assessment was conducted for 3 days. Incidence of Grade 1 pressure injuries on the respondent's skin or mucous membranes with a mean score of Neonatal Skin Risk Assessment Scale < 13 and average Braden Q score > 15 were observed. Health devices that caused pressure injuries on respondents were: ETT (13%), OGT (12%), NGT (11%), and SpO2 probe (6%). There were no significant differences between the control group and intervention group in terms of the number of pressure injury incidences. Skin trauma and pressure injuries caused by medical devices were within the low-risk category; therefore, nurses should not be complacent with the NSRAS and Braden Q scores in preventing pressure injuries. Further research is recommended to improve the power of related research and development in risk assessment of pressure injuries caused by medical devices in children.